2017
DOI: 10.1007/s00226-017-0909-6
|View full text |Cite
|
Sign up to set email alerts
|

Transversal mechanical properties of surface-densified and hydrothermally modified needle fir wood

Abstract: Hydrothermal-mechanical (HTM) treatment is a combined action of temperature, moisture, and mechanical loads. Various kinds of HTM processes have been developed to produce eco-friendly modified wood products. Among these modification technologies, a combination of surface densification and hydrothermal post-treatment is a promising option that can be used to enhance plantation wood properties and generate value-added softwood products. This paper aimed to investigate the transversal dynamic transversal modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…For sandwich-compressed wood, the compressed layer is identified as the part with density of 20% higher than the maximal density of the control specimen; the region whose density is less than the maximal density of the control is considered as the uncompressed layer; regions between the compressed layer and uncompressed layer is defined as the transition layer. In this paper, the densities of compressed layer, uncompressed layer and transition layer were in the ranges of > 0.59 g/cm 3 , < 0.49 g/cm 3 , 0.49-0.59 g/cm 3 , respectively. Position of compressed layer(s) is defined as the distance from the edge of compressed layer(s) to the associated surface(s) of the compressed wood.…”
Section: Determination Of Compressed Layer(s)mentioning
confidence: 79%
See 2 more Smart Citations
“…For sandwich-compressed wood, the compressed layer is identified as the part with density of 20% higher than the maximal density of the control specimen; the region whose density is less than the maximal density of the control is considered as the uncompressed layer; regions between the compressed layer and uncompressed layer is defined as the transition layer. In this paper, the densities of compressed layer, uncompressed layer and transition layer were in the ranges of > 0.59 g/cm 3 , < 0.49 g/cm 3 , 0.49-0.59 g/cm 3 , respectively. Position of compressed layer(s) is defined as the distance from the edge of compressed layer(s) to the associated surface(s) of the compressed wood.…”
Section: Determination Of Compressed Layer(s)mentioning
confidence: 79%
“…In traditional wood compression, high compression ratio is required for the satisfactory properties of compressed wood in terms of surface density and hardness [1]. While wood surface compression is an essential pathway for enhancing the density and hardness of wood surfaces [2][3][4][5][6]. It has been reported that polar wood preheated at 180 °C for 350 s can be softened and thus compressed into the required compressed wood with a relatively high surface density [2], but cell walls inside the compressed wood are also compressed as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, wood hemicellulose and partly lignin were degraded in the pretreatment with NaOH/NaSO 3 solution, which was confirmed by FTIR results, and allowed the wood easier to be compressed in the hot-processing treatment. Meanwhile, the much higher density and strength of the wood could be achieved under sufficient compressibility [38]. This probably mainly attributed to synergistic effect of degradation of hemicellulose and lignin in the chemical pretreatment and recombination of wood cells during the hot-pressing process.…”
Section: Ftir Analysismentioning
confidence: 99%
“…When the preheated time is further extended to 12 min, the compressed layer becomes the one with only one density peak, but the density peak is lower than that of compressed layer(s) obtained from preheating for 4 or 8 min. During the preheating, water/ moisture move from higher moisture content areas to lower moisture content areas through cell cavities and pit openings, water/moisture, and heat transfer from the wood surfaces to the wood interior, and new temperature and moisture gradients were formed in the compression direction of wood [22]. Once pressure is loaded on the wood, a new yield stress gradient is formed, yielding various positions of compressed layers, and the distance between the wood surface and the associated edge of compressed layer (the compressed layer position) gradually increases, and the compressed layers eventually integrate to form a single layee in the wood center.…”
Section: Structural Formation Of Sandwich Compressed Woodmentioning
confidence: 99%